Motivation in werstern culture: a psychological perspective - Valeriya Zabolotna, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The most actual question for modern social structures is how to maintain constant motivation of the participants at the high level, given that biologically adaptation reinforce the desire to conserve resources (whether physical or mental). Approaches to the study and management of this phenomenon in Western culture continuously changing over the last 150 years, based on researches, theories and practices applied in organizations and which have demonstrated positive results. In general, today it is clear that the era of mechanical models organizations ended and in the competitive world began the new era of biological models which intensively uses knowledge, information flows and technology. Based on this perception changes in the perceived sources of motivation occur.
Keywords: motivation; level of consciousness; changes; competence; delegation of authority